Traumatic pseudoaneurysm of the peroneal artery following lower extremity fracture – A case report and review of the literature - Christian Thomas Hübner; Philipp Vetter; Sandro-Michael Heining; Hans-Christoph Pape; Christian Hierholzer (Trauma Case Reports)
This report documents a rare case of arterial aneurysm following a closed midshaft tibial and fibular fracture. Briefly, a 17-year-old female suffered a traumatic lower extremity fracture and was treated by intramedullary nailing of the tibia. After an uneventful postoperative course, she noted a painful and pulsating swelling of the lateral aspect of the lower extremity about 2 weeks post op. Diagnostic ultrasound confirmed formation of traumatic pseudoaneurysm of the peroneal artery adjacent to the fibular fracture. Subsequent endovascular treatment using coil-embolization was successful. Bony healing occurred in a timely fashion and the patient returned to pain free semi-professional sports activities.